Optimizing odor-baited trap methods for collecting mosquitoes during the malaria season in The Gambia - Jawara, M; Smallegange, R.C; Jeffries, D; Nwakanma, D.C; Awolola, T.S; Knols, B.G.J; Takken, W; Conway, D.J (PloS one, 2009)
Baited traps are potential tools for removal or surveillance of disease vectors. To optimize the use of counter-flow traps baited with human odor (nylon socks that had been worn for a single day) to capture wild mosquitoes in the Gambia, investigations were conducted at a field experimental site. Experiments employing Latin square design were conducted with a set of six huts to investigate the effects of the following on overnight mosquito trap catches: (1) placement of traps indoors or immediately outdoors, CO(2) supply, and presence of a human subject in the hut; (2) trap height for collecting mosquitoes immediately outdoors; (3) height and distance from hut; (4) interaction between multiple traps around a single hut and entry of mosquitoes into huts. A total of 106,600 adult mosquitoes (9.1% Anopheles gambiae s.l., 4.0% other Anopheles species) were collected over 42 nights. The high numbers of An. gambiae s.l. and other mosquitoes collected by odor-baited traps required CO(2) but were largely independent of the presence of a person sleeping in the hut or of trap placement indoors or outdoors. For outdoor collection that is considered less intrusive, traps opening 15 cm above the floor of the hut veranda were more highly effective than traps at other heights or further from the hut. There was no significant evidence of saturation or competition by the traps, with multiple traps around a hut each collecting almost as many mosquitoes as single traps and no effect on the numbers of mosquitoes entering the huts. The outdoor trapping protocol is convenient to compare attractiveness of different odors or synthetic chemicals to malaria vectors and other wild mosquitoes. The finding that such traps are reliably attractive in the presence or absence of a human volunteer encourages their potential development as standardised surveillance tools.